Genetic Linkage and Quantitative Trait Loci (QTL) Mapping in Hevea-Latex Timber Clones - Atan, Safiah (2011)
Hevea brasiliensis or Rubber is the second most important commodity crop in Malaysia after Oil Palm. This crop has been extensively cultivated in South-east Asia region but has its origin from the Amazon Basin of South America. This crop is propagated commercially by hand pollination and bud-grafting using selected parental clones and has caused inbreeding depression as seen in the low fruit set per pollination (average of ten seeds per 100 flowers pollinated). Estimation of genetic variability became necessary with the incorporation of the new prospected materials from Brazil compared to the classical cultivated clones. Thus molecular markers were incorporated into the studies on Hevea, since no distinct morphological traits exist between H. brasiliensis clones. In this study, comparisons of genetic linkage maps between two Hevea populations were conducted. Genetic linkage maps of clones RRIM 937, RRIM 600, PB 5/51 and IAN 873 were constructed with molecular markers generated using the Amplified Fragment Length Polymorphism (AFLP) technique. These maps covered 7.2-13% of the estimated genome length which is between 2000 cM to 3000 cM. Genetic maps for RRIM 937 and RRIM 600 showed that the maps did not have the basic number of linkage groups of 18. One explanation is that both clones are closely related in which RRIM 600 the re-current parent is both paternal and maternal. Thus molecular markers that are generated were mostly monomorphic and uninformative in genetic map construction. Meanwhile, genetic maps for clones PB 5/51 and IAN 873 spans 18 and 17 linkage groups respectively. These two clones are quite distantly related i.e IAN 873 has a Brazilian clone, FA 1717 for a paternal parent. Nevertheless, the amount of markers generated for this population was not enough to create a dense coverage for the maps. Due to the paucity of the markers generated for all four clones, the majority of the markers were placed on Group 1 whilst the other linkage groups had 2-4 markers each and most of them were located near the centromere. Locations of two Quantitative Trait Loci (QTLs) associated to susceptibility to Corynespora cassiicola were on linkage group 1 of clone IAN 873. None were found on the PB 5/51 genetic map. The Logarithim of Odds (LOD) score for these QTLs were insignificant due to the small number of pro genies used in the disease screening. Using the interval mapping approach, a major QTL (Cc1-1ian) was located on Group 1 of IAN 873, which explained 10.1% of the phenotypic variation and a minor QTL (Cc1-2ian) was located on the same linkage group, explaining 5.2% of the phenotypic variation. The subsequent Multiple-QTL Model (MQM) analysis was also conducted and did not reveal any new QTLs on any other linkage groups but was able to pin-point the positions of the QTLs closer to markers P2E2M13205 and P2E2M13198/ P2E2M13220 for Cc1-1ian and marker P2E2M13192 for Cc1-2ian. The analysis of the differential display patterns obtained from 30 primer combinations had produced 14 specific cDNA fragments and it appears that more genes were expressed in both tolerant and susceptible clones after 72 h of inoculation. Genes are being turned on upon infection and the tolerant clones seem to have more genes expressed at this stage and cDNAs extracted from the Differential Display Reverse Transferase (DDRT) gels had high homology with stress-related genes. Differential display products excised from Hevea clones that were susceptible to C. cassiicola had strong homology to Populus x canadensis mRNA for putative histidine-containing phosphotransfer protein 2 (hpt2 gene) which is involved with osmotic stress and cell growth, disease resistance protein (RPM1) found in castor beans (Ricinus communis), Alternanthera philoxeroides (Aligator weed) salinity-induced protein (SI10) and EST from severe drought-stressed Populus leaves. It is possible that in Hevea, the gene related to osmotic stress is turned off upon release of cassiicolin, resulting in the collapse of the cells and these genes could be induced locally rather than systematically as the colonization of the pathogen only occurs when cassiicolin is present. A large portion of the cDNA extracted from the DDRT gel (82%) lacked any similarity to any known proteins (data not shown). They were classified either as transcripts lacking similarity to any known sequences or as transcripts not producing any hits. These genes of unknown function could probably be transcripts that are specifically expressed in leaves during stress/defense related conditions.